Discovery and Preclinical Characterization of Fulacimstat (BAY 1142524), a Potent and Selective Chymase Inhibitor As a New Profibrinolytic Approach for Safe Thrombus Resolution - Fürstner, Chantal; Ackerstaff, Jens; Meier, Heinrich; Straub, Alexander; Mittendorf, Joachim; Schamberger, Jens; Schäfer, Martina; Börngen, Kirsten; Jörißen, Hannah; Zubov, Dmitry; Zimmermann, Katja; Tersteegen, Adrian; et al. (Journal of medicinal chemistry, 2025)
Chymase is a serine-protease produced by mast cells. In the past few decades, its role in fibrotic diseases triggered the search for orally available chymase inhibitors. Aiming at reducing adverse cardiac remodeling after myocardial infarction, our research efforts resulted in the discovery of fulacimstat (BAY 1142524). While clinical trials did not demonstrate efficacy in this indication, the recent discovery of a new unexpected biological role of chymase spurred a revival of interest in chymase inhibition: chymase was shown to inactivate plasmin within fibrin-rich clots. Chymase inhibitors are now considered as potential profibrinolytic drugs with low bleeding risk and therefore exceptional safety for the treatment of acute thrombosis settings such as stroke, pulmonary embolism, or venous thrombosis. This article describes the chemical optimization journey from a screening hit to the discovery of fulacimstat (BAY 1142524), a selective chymase inhibitor with a good safety profile, as well as its preclinical in vitro and in vivo characterization.